2015
DOI: 10.4103/0975-1475.172447
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of palatal rugae pattern in establishing identification and sex determination in Nalgonda children

Abstract: Background:Establishing individual identification of a decedent only by dental means is a mammoth task in forensic odontology. Palatal rugae's uniqueness, its resistance to heat, and stability throughout life have been proved by its use as an alternative aid in individual identification where comparison of fingerprints and other records is difficult.Aims and Objectives:The aim of the present study was to analyze the role of palatal rugoscopy in personal identification and sex determination of Nalgonda pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
2
12
2
3
Order By: Relevance
“…11 Observing the length of rugae, it appears that primary rugaes are most prevalent than secondary and fragmented rugaes. 12 Examining the types and origins of palatal rugae according to the Lysell classiications, the study of Beatrice's (2013) showed that the palatal rugae of males is diferent from that of females. Primary and Secondary rugaes are all found in males compared to females, whereas fragmented rugaes are more common in females than males.…”
Section: Resultsmentioning
confidence: 99%
“…11 Observing the length of rugae, it appears that primary rugaes are most prevalent than secondary and fragmented rugaes. 12 Examining the types and origins of palatal rugae according to the Lysell classiications, the study of Beatrice's (2013) showed that the palatal rugae of males is diferent from that of females. Primary and Secondary rugaes are all found in males compared to females, whereas fragmented rugaes are more common in females than males.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology and position of the palatal rugae hardly change after diseases, trauma or chemical corrosion. Genetic, unique and stable human palatal rugae patterns contribute to forensic identification (Shetty et al, 2015;Thabitha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of forensic medicine, palatal rugae patterns contribute to forensic identification (Santos et al, 2011Rath & Reginald, 2014Poojya et al, 2015;Thabitha et al, 2015). There are controversies about whether diverse morphological changes of palatal rugae patterns after clinical orthodontic treatment can influence forensic identification.…”
Section: Discussionmentioning
confidence: 99%